Phasing out coal: A just transition approach - Béla Galgóczi (European Trade Union Institute (ETUI), 2019)
The clock is ticking and time is running short for us to have a realistic chance to get climate change under control and prevent it becoming irreversible and selfsustaining. Phasing out coal is widely seen as a 'low hanging fruit' of climate policy commitments in the move towards a net zero carbon economy by 2050. Coalbased energy generation and use made up 15 per cent of total EU greenhouse gas emissions in 2017; while, at the same time, these have a rather low share in the total economy and employment. On the other hand, coal-dependent activities are concentrated in a small number of European regions where they provide the main basis for the economy, employment and the livelihoods of people. If properlydesigned just transition policies can have a meaningful effect, then coal transition is the right place to start. The focus of this working paper is to find out what a just coal transition might look like in practice. After summing up the role of coal in the European economy and in employment, the current employment structure of the broader coal sector will be examined in greater detail. Then, by discussing the drivers and challenges of coal transition, we will provide an insight into the phasing out of coal and the related introduction of just transition policies in a number of EU member states. This working paper will conclude that, in order to fulfil mid-century climate policy targets and manage a successful phase-out of coal in the energy sector, specific and targeted just coal transition policies should be applied.
Keywords: 330; mining policy; structural change; Sustainable development; employment structure; job security; EU policy; EU countries; Bergbaupolitik; Strukturwandel; Nachhaltige Entwicklung; Beschäftigungsstruktur; Beschäftigungssicherung; EU-Politik; EU-Staaten